Doubling immunochemistry laboratory testing efficiency with the cobas e 801 module while maintaining consistency in analytical performance - Findeisen, Peter; Zahn, I.; Fiedler, G. M.; Leichtle, A. B.; Wang, S.; Soria, G.; Johnson, P.; Henzell, J.; Hegel, J. K.; Bendavid, C.; Collet, N.; McGovern, M.; et al. (Clinical biochemistry, 2018)
OBJECTIVES: The new immunochemistry cobas e 801 module (Roche Diagnostics) was developed to meet increasing demands on routine laboratories to further improve testing efficiency, while maintaining high quality and reliable data. - DESIGN AND METHODS: During a non-interventional multicenter evaluation study, the overall performance, functionality and reliability of the new module was investigated under routine-like conditions. It was tested as a dedicated immunochemistry system at four sites and as a consolidator combined with clinical chemistry at three sites. - RESULTS: We report on testing efficiency and analytical performance of the new module. Evaluation of sample workloads with site-specific routine request patterns demonstrated increased speed and almost doubled throughput (maximal 300 tests per h), thus revealing that one cobas e 801 module can replace two cobas e 602 modules while saving up to 44% floor space. Result stability was demonstrated by QC analysis per assay throughout the study. Precision testing over 21days yielded excellent results within and between labs, and, method comparison performed versus the cobas e 602 module routine results showed high consistency of results for all assays under study. In a practicability assessment related to performance and handling, 99% of graded features met (44%) or even exceeded (55%) laboratory expectations, with enhanced reagent management and loading during operation being highlighted. - CONCLUSION: By nearly doubling immunochemistry testing efficiency on the same footprint as a cobas e 602 module, the new module has a great potential to further consolidate and enhance laboratory testing while maintaining high quality analytical performance with Roche platforms.
Gesehen am 20.04.2020